Determining the Age of the Parasitic Invasive Fly Philornis downsi Using the Fluorescent Pigment Pterin - Colwitz, Alyssa; Freund, Deborah A. (My University, 2017)
Philornis downsi, an invasive fly in the Galapagos Islands, negatively affects land bird species. Fly eggs in bird nests hatch into parasitic larvae that feed on the blood and flesh of chicks, decreasing fledgling success. Little is known about the reproductive biology of Philornis; learning how they survive eight months of the “dry” season, when known hosts are not breeding, may help determine a control method. If they use other hosts, we will find wild flies younger than eight months old at the beginning of the “rainy” season. The pigment pterin, found in the eyes of Philornis, accumulates with age. Lab raised flies of known age were used to establish an average rate of accumulation, serving as a way to age flies, but it was not clear if this same rate applied to wild flies exposed to natural sunlight. Pupae collected from nests were kept in the lab until emergence. Half were raised in outside cages and half in the lab. Flies were decapitated at known ages and pterin was measured. There were no significant differences between pterin levels in outside and lab groups at the same ages, confirming the validity of using our aging methods for field-caught flies.
Color poster with text, photographs, and graphs.
Keywords: Parasites; Galapagos Islands; Age estimation; Posters